Cognitive motor interference during walking in multiple sclerosis using an alternate-letter alphabet task - Learmonth, Yvonne C; Sandroff, Brian M; Pilutti, Lara A; Klaren, Rachel E; Ensari, Ipek; Riskin, Barry J; Holtzer, Roee; Motl, Robert W (Archives of physical medicine and rehabilitation, 2014)
To examine cognitive motor interference (CMI) during walking using a simple, standardized, and well-refined alphabet dual-task (DT) paradigm in individuals with multiple sclerosis (MS) in whom cognitive and walking impairment often co-occur. A single time point, cross-sectional study. A university clinical laboratory. Individuals with MS (N=61; mean age ± SD, 50.8±9.3 y) performed 4 walking trials over a 4.6-m walkway to determine gait parameters. Not applicable. Gait parameters were assessed over 4 walking trials. The first 2 walks involved the single task (ST) of walking only; the second 2 walks involved participants performing the DT of reciting alternate letters of the alphabet while walking. The gait parameters recorded during the ST and DT walks were used to compute a dual-task cost (DTC) of walking (% change in gait parameter between ST and DT walks) as a metric of CMI. Our multivariate analysis with univariate follow-ups indicated CMI during walking based on slower velocity (ηp(2)=.59; F=84.6; P<.001) and cadence (ηp(2)=.46; F=51.6; P<.001), shorter step length (ηp(2)=.38; F=36; P<.001), and increased step time (ηp(2)=.34; F=31; P<.001) and double-support time (ηp(2)=.31; F=27.3; P<.001) in DT versus ST conditions. The DTC of walking for the gait parameters was not correlated with clinical (disability, disease duration) and demographic (eg, education, age) factors (all |r|≤.240). The alphabet DT paradigm is easily administered and well refined. We highlight its ability and acceptability to determine CMI during walking in people with MS, independent of disease status.